How Do Mobile Wallets Improve Sustainability in Payment Services? A Comprehensive Literature Review - AYSUNA TÜRKYILMAZ, CEYDA (My University, 2022)
Easy access to the Internet, smartphones, and mobile-based banking change customer shopping intentions. As a crucial component of financial technology (Fintech), mobile wallets enable customers to shop via smartphones. Mobile wallets present a cashless transactional method, costefficient services, and traceable options that improve sustainability in payment services. Over the last decade, mobile wallet services have evolved and attracted considerable attention from customers and companies. Due to the need for a comprehensive mobile wallet literature survey, this article aims at filling this research gap by covering articles published between 2012 and 2022 over the Scopus, Web of Science, and Science Direct databases. A clear filtering policy was conducted to observe the related article topics. Thus, 128 articles that met the inclusion and exclusion criteria were analyzed. Moreover, the articles were initially classified into three main groups, which was performed via scanning and categorizing all studies in the last ten years from different databases. In addition, the literature was systematically reviewed, providing a better understanding of mobile wallets and contributing to the literature by researching how this service can be improved for payment services with a focus on sustainability. The conducted literature review revealed that mobile wallets could be promoted in terms of environmental traceability, customer lifetime value, and security.
Keywords: Endüstri Mühendisliği; Mühendislik ve Teknoloji; Industrial Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ENDÜSTRİYEL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, INDUSTRIAL; mobile wallet; e-wallet; sustainability; literature review